GASTRIC CONDUIT NECROSIS IN ESOPHAGEAL SURGERY (International Research Journal of Medical Sciences and Health Care, 2024)
This study aims to investigate the occurrence, risk factors, clinical presentation, and management of gastric conduit necrosis following esophageal reconstruction, providing insights into its impact on patient outcomes and strategies for prevention and treatment. A retrospective analysis was conducted on patients who underwent esophageal reconstruction with gastric conduit creation between January 2010 and December 2023. Clinical records, including surgical notes, postoperative outcomes, and follow-up data, were reviewed to identify cases of gastric conduit necrosis. Risk factors such as surgical techniques, preoperative conditions, and postoperative complications were analyzed. Management approaches, including surgical interventions and conservative treatments, were also assessed.